Frequency Analysis of Annual Maximum Flood for Segamat River - Noor Suraya, Romali; Zulkifli, Yusop (EDP Sciences, 2017)
Several major floods had occurred in the last few decades in Segamat, causing extensive damage to properties and harm local community. For the purpose of flood risk management, this study estimated the average recurrence interval (ARI) and peak flows associated with the ARI based on the distributions of annual peak flow. The flood frequency analysis was performed for flood series data of Segamat River, at Sg. Segamat gauging station (Site 2528414) for the years 1960 – 2011. Five distribution models, namely Generalized Pareto, Generalized Extreme Value, Log-Pearson 3, Log-Normal (3P) and Weibull (3P) were tested for the 52 years flood series data. The goodness of fit test (GOF) of Kolmogorov-Smirnov (K-S) was used to evaluate and estimate the bestfitted distribution. The results obtained using Generalized Pareto distribution provided the best fit, followed by Generalized Extreme Value, Log-Pearson 3, Log-Normal (3P), and the least for Weibull (3P). The estimated peak flows for Segamat River for 50, 100 and 200 ARIs are 1362.2 m3/s, 1914 m3/s and 2642 m3/s respectively. Results can be useful as a reference for further/future flood risk assessment works in the study area.